EFFECT OF FINANCIAL LITERACY AND RISK PERCEPTION ON STUDENT INVESTMENT DECISIONS IN JAKARTA - Saputro, Rizky Eko Harry; Lestari, Diyan (International Business Management - Universitas Ciputra, 2019)
This study aims to determine the effect of financial literacy and risk perception on student investment decisions in Jakarta. This study used a quantitative approach through questionnaires with as many as 120 respondents taken as sample which is obtained by using non-probability sampling technique and purposive sampling method. The research data is processed with SPSS, where the hypothesis is analyzed using t-test and multiple linear regression analysis. The results of this study indicate that financial literacy variable have a significant effect on investment decision, based on the t-test result which shows that t-count is higher in comparison to ttable (8,433>1,98045). Similarly, the risk perception variable have a significant effect on investment decision, which is shown by the higher tcount compared to t-table (2,319>1,98045).